Global Trends and Emerging Perspectives In Cooperative Learning: A Systematic Literature Review and Bibliometric Analysis - Kurniawan Arizona; Joni Rokhmat; Agus Ramdani; Gunawan Gunawan; A A Sukarso; Ramdhani Sucilestari (Indonesian Publication Center, 2024)
This study aims to examine the evolution of cooperative learning research by employing a systematic literature review (SLR) combined with bibliometric analysis. The method involves analyzing published articles, identifying trends, influential authors, key institutions, and the geographical distribution of research. The results reveal a significant increase in the number of publications on cooperative learning, especially since 2007, with major contributions from countries like the United States, China, and Spain. The study also highlights the integration of educational technology and cultural considerations in cooperative learning practices. The discussion emphasizes the role of collaboration in improving educational outcomes and addresses the adaptation of cooperative learning strategies across various cultural contexts. In conclusion, cooperative learning remains a vital pedagogical approach, and future research should focus on exploring its intersection with technology and its adaptability in diverse educational environments.